A review of the genus Ancylosis Zeller, 1839 (Lepidoptera: Pyralidae: Phycitinae) from Ukraine - Bidzilya, Oleksiy; Budashkin, Yuriy; Yepishin, Viktor (Zootaxa, 2019)
Nine species of Ancylosis are recorded from Ukraine. Ancylosis larissae sp. nov. related to A. hellenica (Staudinger, 1870) and A. rhodochrella (Herrich-Schäffer, 1852), is described from Crimea. Ancylosis albicosta (Staudinger, 1870) is reported from Ukraine for the first time. Ancylosis albidella Ragonot, 1888, A. syrtella (Ragonot, 1887), A. rhodochrella, A. harmoniella (Ragonot, 1887) and A. monella Roesler, 1973 are removed from the list of Pyralidae of Ukraine due to misidentifications. The host plants for A. sareptalla (Herrich-Schäffer, 1861) and A. substratellum (Christoph, 1877) comb. nov. are recorded for the first time. New host plant is recorded for A. roscidella (Eversmann, 1844). The diagnoses for all species known from Ukraine are provided. The adults and genitalia of both sexes are illustrated for all Ukrainian species and some closely related species from adjacent territories. A key to the species is given based on external characters and the genitalia of both sexes. The female genitalia of A. deserticola (Staudinger, 1870), A. hellenica (Staudinger, 1870), A. sabulosella (Staudinger, 1879) as well as the male genitalia of A. pallida (Staudinger, 1870) are described and illustrated as they have been dealt incorrectly in literature. The status of A. albidella and the records of this species from Europe are discussed. The new synonymy is proposed: Ancylosoma Roesler, 1973 syn. nov. of Ancylosis Zeller, 1839 and A. sareptalla gulbaharensis Roesler, 1973 syn. nov. of A. sareptalla (Herrich-Schäffer, 1861). Ancylosis decolorella (Ragonot & Hampson, 1901) spec. rev., stat. nov. is taken out from synonymy with A. sabulosella. The lectotype of Myelois deserticola Staudinger, 1870 is designated.